Effect of TaC/Ti/Si3N4 Hard Ceramics on Mechanical and Microstructural Behaviour of AA7075 Processed through Stir Casting Process - J. Pradeep Kumar; D. S. Robinson Smart; Stephen Manova; N. Ummal Salmaan (Advances in Materials Science and Engineering)
A liquid metallurgical stir casting route was utilized for developing aluminium alloy (7075) matrix composites blended with fluctuating wt% of silicon nitride (Si3N4), tantalum carbide (TaC), and titanium (Ti) for sake of generating a profitable composite with enhanced properties. The physical, microstructural, and mechanical characteristics such as density, high temperature tensile, fatigue, and time-dependent creep experiments were conducted and evaluated. SEM microstructural examinations were performed on the composite samples and proved that there was a good interfacial bonding and uniform dissemination among the reinforcement particulates in the matrix. Physical characteristics were analysed and the outcomes showed that AA7075 blended with 1 wt% TaC, 8 wt% Si3N4, and 0.5 wt% Ti proved higher experimental and theoretical densities of 3.2464 g/cm3 and 3.3038 g/cm3, respectively, with maximum porosity of 1.7758%. At 30°C, the tensile properties of the developed MMCs showed improved ultimate tensile strength (UTS) of 137.64 N/mm2. Beyond 100°C, AA7075 reinforced with 0.75 wt% TaC, 6 wt% Si3N4, and 1 wt% Ti proved to have a higher strength of 232.17 N/mm2. Fatigue properties of the developed MMCs discovered were found to be reformed when proportionate to the base alloy by operating at 14 × 103 cycles at the stress of 42.72 MPa. Time-dependent creep analysis of the developed MMCs found to be advanced due to the addition of tough ceramic particulates.